1976
DOI: 10.1002/ccd.1810020207
|View full text |Cite
|
Sign up to set email alerts
|

Aortic stenosis, angina pectoris, coronary artery disease

Abstract: The data from 88 patients (pts) with aortic stenosis (AS) were reviewed to determine relationships between angina pectoris (AP) and coronary artery disease (CAD). Results of surgery performed in 81 of these pts was analyzed. All pts had coronary arteriograms, and lesions greater than or equal to 50% were considered significant. Fifty-nine pts had an aortic valve gradient measured at catheterization greater than or equal to 40 mmHg, and in 29 pts, AS was confirmed at operation. Sixty-eight pts (77%) experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 10 publications
(1 reference statement)
4
9
0
Order By: Relevance
“…In comparison to mitral valve disease, aortic valve disease and combined lesion have significantly higher chance of coronary artery disease (p=0.001). The findings are supported by Moraski RE et al [12] and Lacy J et al [13] CONCLUSION Overall prevalence of significant coronary artery disease in patients with valvular heart disease is 14.28% in this part of the country. Prevalence of coronary artery disease in rheumatic valvular heart disease is 9.26%, while in nonrheumatic valvular heart disease it is 44.44%.…”
Section: Discussionsupporting
confidence: 64%
“…In comparison to mitral valve disease, aortic valve disease and combined lesion have significantly higher chance of coronary artery disease (p=0.001). The findings are supported by Moraski RE et al [12] and Lacy J et al [13] CONCLUSION Overall prevalence of significant coronary artery disease in patients with valvular heart disease is 14.28% in this part of the country. Prevalence of coronary artery disease in rheumatic valvular heart disease is 9.26%, while in nonrheumatic valvular heart disease it is 44.44%.…”
Section: Discussionsupporting
confidence: 64%
“…In the study by Chun et al, 82 patients with MS underwent CAG, and 21 patients (26%) were found to have CAD [7]. Similar studies on patients with aortic stenosis reported a 56% prevalence rate for CAD [8],[9]. In the study by Shaikh et al that evaluated 144 patients who underwent replacement of mitral valve, aortic valve or both, there was evidence for severe CAD in 32.9% of the patients who underwent MVR, 31.9% of the patients who underwent AVR, and 25% of the patients who underwent the replacement of both valves [10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are some patients without angina who still have significant coronary obstruction.3 [8][9][10] In patients being considered for valve surgery it is generally accepted that the presence of angina is an indication for coronary arteriography as part of the preoperative investigations.' 8 …”
mentioning
confidence: 99%